2003
DOI: 10.2166/wp.2003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Integrated water management in the South Pacific: policy, institutional and socio-cultural dimensions

Abstract: As scarce water supplies in urban environments come under increasing pressure, water managers are forced to widen technical analyses to incorporate issues related to water governance. The concept of integrated water management has been developed to highlight that social, institutional and economic issues, in addition to technical and ecological considerations, need to be considered concurrently. In this paper, the integrated water management framework is used to highlight some of the social and institutional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…For example, Keen (2003) used the integrated water management framework to guide a critique of policy, institutional and socio-cultural dimensions of water, sanitation and water resources management in Suva, Fiji. Wutich et al (2014) concluded that there is a general willingness to engage in 'soft pathway' solutions (water conservation, efficiency and allocations)…”
Section: Management and Governancementioning
confidence: 99%
See 4 more Smart Citations
“…For example, Keen (2003) used the integrated water management framework to guide a critique of policy, institutional and socio-cultural dimensions of water, sanitation and water resources management in Suva, Fiji. Wutich et al (2014) concluded that there is a general willingness to engage in 'soft pathway' solutions (water conservation, efficiency and allocations)…”
Section: Management and Governancementioning
confidence: 99%
“…The first was the importance of considering context, also mentioned in the Emergency WaSH and intervention strategies section. This included the need to harmonize governance and management approaches with local socio-cultural factors (Carden 2003;White et al 2008;Wutich et al 2012), the importance of understanding water and resources ownership customs and conflicts (Keen 2003;Storey & Hunter 2010;Wutich et al 2012), the value of integrating indigenous knowledge and values with best practices (Smith Jr 2008), and the need for locally-appropriate sustainable technologies (South et al 2004;Smith Jr 2008).…”
Section: Management and Governancementioning
confidence: 99%
See 3 more Smart Citations